JOB MOTIVATION, WORK-FAMILY CONFLICT, AND JOB SATISFACTION OF FORMAL WORKING MOTHERS DURING COVID-19 PANDEMIC - Meida Eka Sovya Melati; Risda Rizkillah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Work from home (WFH) policies can fade the boundaries between family and work matters, reduce work motivation, and create uncertainty that impacts job satisfaction. This study aims to analyze the effect of work motivation and work-family conflict on job satisfaction of formal working mothers during the Covid-19 pandemic. This study used a cross-sectional research design. The selection of research locations was chosen purposively, namely DKI Jakarta and West Java, because these two provinces were the two provinces that contributed the most Covid-19 cases in Indonesia. Data were obtained by self-administered using a questionnaire that was distributed online. The sampling technique was done by voluntary sampling. The respondents of this study were 99 formal working mothers with intact families who have school-age children (6-12 years). Correlation test results show a relationship between intrinsic work motivation, extrinsic work motivation, and work-family conflict with job satisfaction. In addition, the regression test results showed that the husband's age and identified regulation positively and significantly affected job satisfaction. The results also showed that during the Covid-19 pandemic, most formal working mothers had job satisfaction in the moderate category.